Ice-phobic honeycomb-like nano SnO2 surfaces: Effect of pretreatment process on sustainable superhydrophobicity - Elham Aghajanpour Amiri; Reza Norouzbeigi; Elmira Velayi (Applied Surface Science Advances, 2024)
Superhydrophobic/Icephobic tin oxide honeycomb-like nanostructures were synthesized on copper surfaces via facile controlled hydrothermal method. Effects of two crucial fabrication parameters including etching treatment variables and presence the seed layer, on the morphology and wettability of the resulted coating were determined. The chemical composition, wettability characteristics, and topographical properties of the samples were characterized by FE-SEM, stylus profilometry, contact angle measurement, and ATR-FTIR analyses. The wettability evaluations confirmed that the tin oxide deposited on the copper oxide (seed layer) exhibited excellent superhydrophobic properties. The prepared hierarchical surfaces showed high water contact angles (CA) as well as 169. 5∘±1∘ with a contact angle hysteresis (CAH) of 5°± 1°. Moreover, the results confirmed that the etching treatment and the presence of the seed layer can promote the morphology to a uniform state. The ice adhesion strength of the obtained superhydrophobic surfaces reached to 30.4 kPa, showing an excellent ice-phobicity. The mechanical resistance and/or sustainability of the optimized sample was also passed successfully under 10 abrasion test cycles.